Design and analysis of the support structure for an open channel flume - Nabil Fikri, Zuiful Zubri (2013)
Open channel flumes which will be built on the ground level need a support structure to minimize the displacement at the sidewall due to the hydrostatic and dynamic pressure of water. The objectives of the study are to evaluate the pressure at the sidewall of the flume, and to design a supports structure for the sidewall of the flume under certain flow conditions. Three basic designs were selected and drawn using Solidwork software and solved with the Autodesk Simulation Multiphysics solver. From the data obtain it shows that Design 1 with 0.5 m breadth, 0.44 m length and 21 of support structure by using Ready Mix Concrete Normal Mix Grade 30 gave the smallest value of wall displacement, and 81.73% effectiveness of the support structure. Simulation result shown that the flume did need a support structure to reduce the displacement of the sidewall. As a conclusion, Design 1 as it gave the desirable result with the acceptable cost involved, effectiveness and economically.